Working Capital Management as a Mediator of the Corporate Governance–Performance Relationship: Evidence from Indonesia - Priyono, Achmad Agus; Widarko, Agus; Saraswati, Ety (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study examines the moderating role of working capital management in the relationship between corporate governance mechanisms, specifically independent commissioners and ownership structure, and firm performance, as measured by Return on Equity (ROE). The analysis is based on panel data from consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Using a quantitative explanatory approach and Partial Least Squares Structural Equation Modeling (PLS-SEM) via WarpPLS 7.0, this study finds that independent commissioners have a significant adverse effect on ROE. At the same time, ownership concentration shows a negative but statistically insignificant effect. Meanwhile, working capital management, proxied by the average payment period (APP), has a significant positive impact on ROE, but does not moderate the relationship between governance mechanisms and firm performance. These findings highlight that structural governance components alone do not guarantee improved financial performance unless accompanied by functional and competent internal financial practices. Theoretically, this study contributes to agency Theory and resource dependence Theory by demonstrating that symbolic governance structures tend to undermine firm value in emerging markets with weak institutional enforcement.